PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBER HEAD TOGETHER (NHT) PADA PEMBELAJARAN FISIKA SISWA KELAS X DI SMA NEGERI NIBUNG - Rina Neneng Ambar Wati; Tri Ariani; Ovilia Putri Utami Gumay (LP4MK STKIP PGRI Lubuklinggau, 2022)
This study aims to determine the completeness of learning outcomes of class X students on Newton's Law material after the Number Head Together (NHT) cooperative learning model is applied at SMA Negeri Nibung. The research method used is in the form of a quasi-experimental. The population is all students of class X IPA SMA Negeri Nibung which accommodates 35 students and as a sample class X. IPA 1 which has 18 students. Data collection is done by using a test technique. The average learning outcomes of physics after the implementation of the Number Head Together (NHT) model is 83.18 and the proportion of students who complete reaches 82.35%. The data collected were analyzed using t-test at a significant level = 0.05 obtained tcount = 1.984 ttable = 0.690, it can be said that student learning outcomes after participating in physics learning with the Number Head Together (NHT) model were significantly completed.